Status of Rice Biochemical Composition under Lodging Treatment - Dulbari, Dulbari; Santosa, Edi; Koesmaryono, Yonny; Sulistyono, Eko (Department of Agronomy and Horticulture, IPB University, 2017)
Extreme weather conditions due to strong wind and high rainfall cause rice lodging. Lodged plants have lower photosynthetic rate and nutrient transport capacity which resulting in lower rice quality. However, physiological process of rice plant under lodging condition is rarely reported. Therefore the objective of this research was to evaluate the biochemical compounds of two rice varieties under artificial lodging treatment. IR64 and HIPA8 varieties were planted at the Experimental Farm in Leuwikopo, Bogor Agricultural University (IPB) in November 2016 to June 2017. At grain filling stage, rice hills were enforced to lodge using manual force until culm break. Analysis of untargeted biochemical compounds was conducted at Research and Development Institute, Laboratory of Regional Health, DKI Jakarta where rice culms from upper and below breaking position were compared. Results showed that rice culms had different biochemical compounds after lodging, especially in fatty acid, terpene, alkane, and steroid group. Lodging culms had a total of 22 to 25 compounds compared to 15 to 17 of the normal plants. It means that lodging stimulated different physiological process in rice plants. A decrease in fatty acid and an increase in the steroid level of lodged plants indicated an increase in oxidative stress of lodging condition. It is possible that low rice grain quality under lodging condition was caused by the changes in the plant physiological processes in response to the environmental stress.Keywords: extreme weather, metabolomics, oxidative stress, rice culm, rice lodging